Encyclopedia of Psychology, Vol. 5. 2000
DOI: 10.1037/10520-106
|View full text |Cite
|
Sign up to set email alerts
|

Middle childhood: Socialization and social contexts.

Abstract: Peer networks and siudents' classroom engagement during childhood and adolescence. In K. Wentzel & J. Juvonen (Eds.), Social motivation: Understanding children's school adjustment (pp. 279312). New York: Cambridge llniversity Press. Leaper, C. (1994). Exploring the consequences of gender segregation on social relationships. In C. Leaper (Ed.), Childhood gender segregation: Causes and consequences (pp. 67-86). San Francisco: Jossey-Bass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
38
0

Year Published

2001
2001
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 3 publications
3
38
0
Order By: Relevance
“…Therefore, the impact of MPH on cognitive–motivational styles may also differ across these factors. Second, children may be more highly motivated by social tasks than by other tasks (Hartup, 1983, 1996). If so, then an increased motivation to perform well may lead to a different pattern of persistence, attributions, and self-evaluations in response to social success and failure as compared with academic success or failure.…”
mentioning
confidence: 99%
“…Therefore, the impact of MPH on cognitive–motivational styles may also differ across these factors. Second, children may be more highly motivated by social tasks than by other tasks (Hartup, 1983, 1996). If so, then an increased motivation to perform well may lead to a different pattern of persistence, attributions, and self-evaluations in response to social success and failure as compared with academic success or failure.…”
mentioning
confidence: 99%
“…In the preschool years, the significant people in a child's life are largely found within the family. With the child's entry into school comes a sharp increase in extrafamilial norms, those of teachers and peers in particular (Costanzo & Shaw, 1966; Hartup, 1983). In addition, schoolwork imparts a new level of significance to success and failure, and there are distinct changes in the means available for evaluating achievement.…”
mentioning
confidence: 99%
“…Negative social concomitants such as these, if found in very young children, could have serious effects on their social and emotional development (Asher & Renshaw, 1981; Hartup, 1983). Yet only two studies were found that examined the issue in young children.…”
mentioning
confidence: 99%
“…Negative social factors not only exacerbate Type A behaviors (cf. Matthews, 1982) but, according to a large body of evidence, can have adverse effects on children's social development (for a review, see Asher & Renshaw, 1981) and on their emotional adjustment in later life (see Hartup, 1983; Putallaz & Gottman, 1982). Teacher utterances were chosen because of their potential to affect the quality of the child's preschool experience (Phillips, 1987).…”
mentioning
confidence: 99%